Furnished cages for laying hens: study of the effects of group size and litter provision on laying location, zootechnical performance and egg quality - A. Huneau-Salaün (Animal, 2011)
The furnished cage is a new housing system for layers. A current trend in furnished cage design is to increase group size and replace the litter box with a mat provided with litter. An experiment was set up to determine the effects of group size and litter provision on laying performance and egg quality of beak-trimmed ISA Brown hens housed in large furnished cages with more than 12 hens. Six treatments, each of 18 furnished cages (768 cm2/hen including nest and litter area) were compared in a 3 × 2 experimental trial: three group sizes (S20 (20 hens per cage), S40 (40) and S60 (60)), with or without feed as litter distributed on the mat of the litter area. The provision of facilities per hen was equal in all treatments. Mortality, laying rate, mean egg weight, feed intake and feed conversion ratio were unaffected by group size over the 53-week laying period, and performance exceeded the ISA production standards. The overall percentage of eggs laid in the nest exceeded 95% except that it was slightly lower in group S20 (92.0% ± 6.4% v. S40: 96.0% ± 3.3% and S60: 96.2% ± 2.7%) leading to a higher proportion of dirty eggs (S20: 1.6% ± 2.2%, S40: 1.4% ± 1.5%, S60: 1.0% ± 1.0%). At 66 to 70 weeks, eggs laid outside the nest had a slightly higher count of mesophilic bacteria on the eggshell (5.0 log CFU/egg ± 0.4) than those laid in the nest (4.8 log CFU/egg ± 0.5) but no difference in contamination was observed between group sizes. Litter provision had no effect on mortality, egg weight or egg quality traits except for a higher proportion of broken eggs in cages with litter (5.3% ± 6.2% v. 4.6% ± 5.7%). Providing hens with feed for litter was associated with a higher laying rate (97.3% ± 3.2% v. 94.8% ± 4.4% at 23 weeks) and an apparent improvement in feed efficiency at the beginning of the laying period (feed conversion ratio based on feed consumption at the trough: 2.18 ± 0.06 with litter v. 2.28 ± 0.09 without litter at 25 weeks). The results of this study showed that a high level of productivity and good egg quality could be obtained in large furnished cages. Further research is needed to assess the impact on hens’ welfare and performance of using more economically competitive substrates than feed for litter.